Penggunaan Metode Triple Exponential Smoothing Tipe Brown dalam Meramalkan Pergerakan Kasus Positif Covid-19 di Kota Padang - Nurul Umiati Husna; Arnellis Arnellis (Journal of Mathematics UNP, 2020)
Abstract — Covid-19 is an infectious disease that caused by SARS-CoV-2 virus. This virus can cause the patient gotten respiratory problems, such as Pneumonis, SARS, and MERS. The amout of     Covid-19 cases have been increased everyday. Therefore, it is necessary to do forecasting for the movement of positive Covid-19 cases in Padang City for the next few days. The purpose of this research was to find out the form of a model for the movement of positive Covid-19 cases in Padang City and to know the results of the movement of positive Covid-19 cases in Padang City. The type of this research is applied research. The method that used in this research is Triple Exponential Smooting Brown Type with the parameter of  that minimize the value of MSE was 0,29.  The results of this research showing the movement of positive Covid-19 in Padang City from August 15, 2020 to August 19, 2020 was 907, 933, 960, 987, and 1016 cases. Keywords — Covid-19, The movement of positive cases, Forecasting, Triple Exponential Smoothing Brown Type.